Upplevelser av aktivitetsbalans hos elever på gymnasieskola med idrottsinriktning - Karlsson,Linnéa; Edinge,Rebecca (2025)
Background: High school students with athletic focus are exposed to a high amount of requirements and pressure, both within school and sports. To combine school and sports can be challenging and have a massive impact on the individual occupational balance. Occupational balance implies a subjective experience of a harmonious mix, with the right amount and variation of activities in everyday life. Occupational balance is important to achieve good health and well-being. Aim: To investigate experiences of occupational balance among students who are between 16 and 18 years old and go to an upper secondary school with athletic focus in Skåne. Method: Qualitative design with an inductive approach. Nine participants were recruited using a convenience selection. Data was analyzed using qualitative content analysis. Results: The result emerged into three main categories: The combination of school and sports creates a stressful but motivating everyday life, Strategies for well-being and occupational balance and Lack of variety of activities. The participants expressed a varied occupational balance that tended to change during the school year and competitive season. Conclusion: The participants sometimes experienced occupational imbalance because of a combination of a lot of training, competitions and schoolwork. Further research is needed to map activity balance to a greater extent and apply and develop occupational therapy in school.
Keywords: Arbetsterapi; aktivitetsvetenskap; aktivitetsbalans; gymnasieskola; ungdomar; idrottsinriktning.